Enhanced electrokinetic remediation of nuclear fission products in organic-rich soils. (February 2021) - Purkis, Jamie M.; Tucknott, Andrew; Croudace, Ian W.; Warwick, Phil E.; Cundy, Andrew B.
Abstract: Electrokinetic remediation, EKR, is technology that circumvents the traditional challenges faced by many existing remediation technologies in low permeability substrates. Cheap, non-toxic additives such as KCl may further help EKR remediation efficiency by increasing electrolyte strength; their use has been reported in concretes, but not soils. Here, we investigate the efficiency of low-energy EKR (with and without electrolyte additives) in the mobilisation of radiostable Cs and Sr in a clayey, organic-rich soil. Soil maturation time and voltage are key factors in determining success of EKR. Although Cs and Sr are effectively mobilised (up to 317 and 330%, respectively) in the electric field in our soils (determined by XRF), maturation time (7 or 45 days) and voltage (15 or 20 V) are key to successful remediation using EKR. We more broadly show that understanding speciation and the local ionic environment of relevant radionuclides within entrained matrices is vital to effective application of this technology. Highlights: Enhanced remediation with cheap, non-toxic additives (KCl) in organic/clayey soils. Target radionuclides are 137 Cs (and 90 Sr) by electrokinetic remediation, EKR. Remediation efficiencies: high (80+% for Cs, 50%+ for Sr) at low voltage. Remediation speed is key; longer than months and Cs becomes intractable. Understanding waste form is vital for removal of Cs in environmental contexts.